ANALISIS KOHESI DAN KOHERENSI WACANA DALAM BERITA KRIMINAL PADA MEDIA ONLINE KOMPAS.COM EDISI APRIL 2020 - ANIS LINGGAR SUSILO ASTUTIK (Jurnal PENEROKA: Kajian Ilmu Pendidikan Bahasa dan Sastra Indonesia, 2021)
A discourse cannot be separated from the elements of cohesion and coherence that emerge as a tool to create a sentence that is aligned, whole, as well as in harmony that is easier to understand. This research aims to find out the cohesion and coherence factors in the discourse in the discourse in criminal news on online media KOMPAS. This research uses descriptive qualitative method. Based on the analysis obtained discourse is the largest unit of language used in communication. The units of language below are sentences, phrases, words, and sounds. Discourse can be both oral and written. One form of use of written discourse is in the writing of criminal news discourse on online media kompas.com. discourse in criminal news is a discourse that contains information about crimes that occur among the community. In such cases criminal news discourse must be written in clear, conctable, and logical language.